1996
DOI: 10.1046/j.1471-4159.1996.66020733.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Induces Apoptosis in Cultured Mesencephalic Neurons

Abstract: The death of dopaminergic and other neurons in primary cultures of the mesencephalon could be induced by treatment with ceramide, as in lymphocytes where it mediates activation by the cytokines tumor necrosis factor-a and interleukin-1 /3 of a novel sphingomyelin-dependent signaling pathway leading to apoptosis. The morphological hallmarks of this form of cell deathbleb formation, cell body shrinkage, nuclear chromatin condensation, and fragmentation-were observed in degenerating neurons. Internucleosomal DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(128 citation statements)
references
References 11 publications
9
118
1
Order By: Relevance
“…The specificity of c 2 -ceramide was evaluated by comparing its effects with those of c 2 -dihydro-ceramide (Biomol Research Laboratory, Plymouth Meeting, PA, USA), an analog lacking the 4 -5 trans double bond in the sphingosine moiety of c 2 -ceramide, which has been shown to be incapable of activating the sphingomyelin pathway in lymphocytes (Bielawska et al, 1993;Obeid et al, 1993) and neurons (Brugg et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The specificity of c 2 -ceramide was evaluated by comparing its effects with those of c 2 -dihydro-ceramide (Biomol Research Laboratory, Plymouth Meeting, PA, USA), an analog lacking the 4 -5 trans double bond in the sphingosine moiety of c 2 -ceramide, which has been shown to be incapable of activating the sphingomyelin pathway in lymphocytes (Bielawska et al, 1993;Obeid et al, 1993) and neurons (Brugg et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The cortex was dissected, mechanically dissociated and plated on polyethyleneimine (1 mg/ml) coated culture wells, in Eagle's basal medium (Eurobio, Les Ulis, France), supplemented with 5% horse serum (HS; Eurobio) and 2.5% fetal calf serum (FCS; Eurobio), at a density of 7.10 5 cells/cm 2 . After 2 days in culture the media was replaced with N5 medium (Kawamoto and Barrett, 1986) with 180mg/l glucose and changed daily; FCS content was reduced to 1%; Ara-C (cytosine arabinoside, 3 M, Sigma, Saint Louis, MO, USA) was added to prevent astrocyte proliferation (our cultures were at least 95% neuronal after this treatment), and MK-801 (1 M, Research Biochemicals International, Natick, MA, USA) to prevent excitotoxicity (Knusel et al, 1990;Brugg et al, 1996). All experiments conformed to French and international guidelines on the ethical use of animals.…”
Section: Primary Cultures Of Mouse Cortexmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased ceramide levels are observed during apoptosis induced by growth factor-withdrawal in neuronally differentiated PC12 cells [32] or cortical neurons [62] and after ischemia in the gerbil hippocampus [41]. Furthermore, apoptosis can be induced by exogenous ceramide treatment of PC12 cells [20,24], mesencephalic [7], hippocampal [40] or cortical neurons [60]. Recently, we have shown that ceramide regulates pro-apoptotic MAP kinase pathways and that JNK and p38 activation is crucial in ceramide-induced neuronal apoptosis in primary cortical neurons [60,61].…”
Section: Introductionmentioning
confidence: 99%